SYMBIOSIS OF MAN AND NATURE: CARPATHIAN LOGGERS IN THE CULTURE OF THE HUTSUL REGION - Poiasyk, Oksana; Lepokhin, Eugene (Mountain School of Ukrainian Carpaty, 2024)
The upper reaches of the Carpathians, where majestic forests and mountain streams offer a distinctive scenery, are home to a unique minority of people – the Carpathian loggers. Timber industry among the Hutsuls, an ethnic group inhabiting the high altitude Carpathians, is an intrinsic part of their culture and pivotal in the environmental balance of the area. The Hutsuls, relying on long-standing traditions, forge a rare symbiosis with nature through their logging activities. Selective felling of trees, the use of traditional processing techniques and wood processing are just a handful of the components of this special system. «Butynar», a Carpathian logger who is an expert at rafting down mountain rivers, is a proficient craftsman. He blends exceptional woodworking skills with the right ones to build reliable rafts that can withstand heavy currents. This craft incorporates the skills of a logger, a shipbuilder and a sailor, transforming rafting of timber not only into a means of conveyance but also into a symbol of Carpathian resilience and craftsmanship. The art of rafting down mountain rivers is the ability to interact harmoniously with nature. With wooden rafts that float effortlessly through the waters pure as driven snow, these craftsmen deftly manoeuvre through mountain rapids and swift currents, with a knack for predicting and adapting to the river’s challenges. Each plash of a paddle is a kind of dancing with nature, a genuine interaction with the river. In addition to navigating the raft, the loggers have a strong awareness of the importance of the environment maintenance to ensure that the generation to come relish the beauty of the Carpathian waters. These people are regular heroes, endowed with strength and resilience enabling them to adapt to any conditions. Their working days, brimming with the sound of axes, blend into a natural concert. The forests of the Hutsul region both provide material resources and play a significant environmental and socio-cultural part. They develop unique ecosystems and are a source of wild herbs, mushrooms and wild animals that provide the Hutsuls with food and raw materials for their crafts. Forests also hold cultural significance for the Hutsuls, as they consider them sacred places steeped in the legends and traditions of their people. The study of ethnocultural traditions, folk crafts and crafts of the Carpathians contributes to the formation of environmental awareness among schoolchildren, encourages the study of the cultural heritage of the highlanders.